Performance Evaluation of Plastic Drum Septic Tanks Equipped with Recycled Nylon Net Biofilters for Domestic Wastewater Treatment in Riverbank Communities - Suharno; Asmadi; Susilawati; Taufik Anwar (Gema Lingkungan Kesehatan, 2026)
Water pollution caused by the direct discharge of domestic wastewater from toilets into watercourses remains a serious environmental health issue, particularly in riverside settlements with limited access to adequate sanitation facilities. This study aims to evaluate the performance of septic tanks made from plastic drums fitted with biofilters made from used nylon netting in improving the quality of domestic wastewater based on the parameters of Biochemical Oxygen Demand (BOD) and Total Suspended Solids (TSS). The study employed a quasi-experimental design with a post-test only control group design, conducted in the villages of Ambawang Kuala and Kuala Mandor B, Kubu Raya Regency. A total of eight plastic drum septic tanks were used, comprising four treatment units fitted with biofilters made from used nylon netting and four control units without biofilters. Wastewater samples were collected from the septic tank outlets and analysed for BOD and TSS using standard laboratory methods. A total of 64 samples were analysed; the data were then processed descriptively and tested using an independent t-test after meeting the assumptions of normality and homogeneity. The results of the study showed that the mean BOD concentration in the treatment group (5.74 mg/L) was lower than that in the control group (7.79 mg/L), whilst the mean TSS concentration in the treatment group was 3.45 mg/L and in the control group 3.17 mg/L. However, there were no statistically significant differences for either the BOD (p=0.227) or TSS (p=0.883) parameters. These results indicate that the use of biofilters made from used nylon netting tends to enhance the reduction in BOD levels, but has not yet yielded a significant improvement in wastewater quality under the conditions of this study. Therefore, this technology has the potential to be developed as an alternative for a simple, low-cost and environmentally friendly sanitation system; however, it still requires design refinements, longer operational periods and testing on a larger scale to ensure its effectiveness.